(3QHjY GdCHQGQ hfUhU GdCNHGQs - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi GSJMeO Edi YHGOg HehLHGJ GdeMGeO eeG CSHZ Ydjge GdahGFO, MeOG edF PGJ GdQLY, hWdGY PGJ GdUOY s
(3BNQgG (B:s
(3Je GdLRA GdKGfi ef QHjY GdCHQGQ HMeO Gddgq s
(3GdfSNI HgG MhGTs
(3HChdgG agQSJ HCHhGH GdcJGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs